PJMHS 2022
DOI: 10.53350/pjmhs22166464
|View full text |Cite
|
Sign up to set email alerts
|

Study the Level of Collagen2-1NO2 (Coll2-1NO2) in Serum of Iraqi Patients with Osteoarthritis

Abstract: Osteoarthritis, often known as OA, is characterized by the degeneration of articular cartilage, limited intraarticular inflammation with synovitis, and peri-articular and subchondral bone changes. This study measured Coll2-1NO2, CRP, ESR, Vitamin D3, Mg, Calcium, and Lipid profiles in OA patients. The current study contained a total of 130 participants, who were divided into two groups. Group1 contained 90 OA patients, and group 2 controls 40; the samples were extracted from females and males, the levels, Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Mutar et al showed that serum Coll2-1NO 2 level increased significantly in both males and females with OA disease. Additionally, their reports agreed with our findings regarding the use of Coll2-1NO 2 as predicative biomarker of OA disease 19 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Mutar et al showed that serum Coll2-1NO 2 level increased significantly in both males and females with OA disease. Additionally, their reports agreed with our findings regarding the use of Coll2-1NO 2 as predicative biomarker of OA disease 19 .…”
Section: Resultssupporting
confidence: 91%
“…Osteoarthritis (OA) is not an autoimmune but a chronic inflammatory disease affecting the joints of humans due to mechanical stress mostly in the knees and the hip 1 . OA is also known as degenerative arthritis and considered as a major health problems that faces the elder people 2 .…”
Section: Introductionmentioning
confidence: 99%